2020
DOI: 10.1111/jgs.16962
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Association Between Team Structure and Health Outcome and Cost by Social Network Analysis

Abstract: Background/Objective To assess the impact of team structure composition and degree of collaboration among various providers on process and outcomes of primary care. Design Cross‐sectional study. Setting Data from 20% randomly selected primary care service areas in the 2015 Medicare claims was used to identified primary care practices. Participants 449,460 patients with diabetes, heart failure, or chronic obstructive pulmonary disease cared for by the identified primary care practices. Measurements SNA network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…In their social network study, Mundt et al [ 24 ] found that high network density was associated with a 38% reduction in hospital days. Similar results were obtained by Kuo et al [ 34 ], who presented positive correlation between network density and hospitalization in the context of COPD, HF, and DM.…”
Section: Discussionsupporting
confidence: 90%
“…In their social network study, Mundt et al [ 24 ] found that high network density was associated with a 38% reduction in hospital days. Similar results were obtained by Kuo et al [ 34 ], who presented positive correlation between network density and hospitalization in the context of COPD, HF, and DM.…”
Section: Discussionsupporting
confidence: 90%
“…The degree centrality was defined as the ratio of edges and vertices per network. The edge density was calculated as the number of existing edges divided by the total number of possible edges per network and can be interpreted as the degree of collaborative care realized in the network [24]. The transitivity measures the interconnectedness of the physicians within a network, which relates to the existence of local clusters.…”
Section: Network Statistics and Correlation Analysismentioning
confidence: 99%
“…The methods for constructing these patient-sharing networks vary depending on the aims of the studies in which they are employed. Most studies of this nature have used routine data to identify all pairs of physicians who are connected through the patients they have in common, and to construct complex networks from these pairs [17][18][19][20][21][22][23][24][25]. Landon et al [18] used SNA to identify networks of physicians who would be suitable candidates for building Accountable Care Organizations (ACOs) in the United States because of their shared patient group.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have proposed various methods to construct physician and medical provider networks to share or transfer patients [ 3 ]. Previous studies on physician networks have examined the relationship between network features and medical cost [ 4 9 ], quality of care [ 10 ], and mortality [ 11 ] as a patient-level medical outcome measure and the relationship between various medical outcomes and network features at the regional level [ 12 ]. Physician networks contain information about medical cooperation and the quality of healthcare.…”
Section: Introductionmentioning
confidence: 99%